Tunneling Magnetoresistance (TMR) on Fe-Al2O3 Nano Granular Film Growth by Helicon Plasma Sputtering - S. Purwanto (Atom Indonesia, 2008)
Fe-Al2O3 nanogranular thin film by helicon plasma sputtering with the variation of Fe content from 0.1 to 0.7 volume fraction have been prepared. The magnetic and magnetoresistance properties were investigated by a Vibrating Sample Magnetometer (VSM) and a Four Point Probe (FPP). The Rutherford BackScattering (RBS) was performed with the SIMNRA software. Conversion Electron Mossbauer Spectroscopy (CEMS) study was also performed to estimate the fraction of Fe and α-Fe2O3 in the granular film. The results suggested that the percolation concentration occured at 0.55 Fe volume fractions, with the maximum Magnetoresistance (MR) ratio of 3%. The present MR ratio that was lower than the previous results may be related to the existence of α-Fe2O3 phase.